Review of case law - Reyes López, Javier Ignacio (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
Supreme Court Ruling 5/2024, of 10 January 2024. Offence of attacking an officer of the authority and reckless driving, in a case also being prosecuted for an offence against public health and a criminal group. 2. Supreme Court Ruling 125/2024, of 08 February 2024. The crime of robbery with violence and injury. Participation: co-authorship. Possibility of assessing the use of a dangerous instrument in both offences. 3. Supreme Court Ruling 99/2024 of 01 February 2024. Offence of serious disobedience of art. 556 of the Penal Code. What is fundamental for integrating the offence is the obstructive attitude and its seriousness, not the injunction to the person under investigation, which is not a required element in the offence, although it may be another element in assessing whether the offence is committed. 4. Supreme Court Ruling 84/2024, of 26 January 2024. Forgery in official documents. Completely false material support of a Colombian driving licence in which both the photograph and all the circumstances and identity data shown on it are true. 5. Supreme Court Ruling 138/2024, of 15 February 2024. Criteria for the validity of the victim’s statement. Persistence of incrimination and assessment of personal circumstances. 6. Supreme Court Ruling 873/2023, of 24 November 2023. The uniqueness of electronic evidence. Collection, custody and traceability. 7. Supreme Court Ruling 140/2024, of 15 February 2024. Police action recording a spontaneous demonstration by a murder suspect. Testimony of reference. Evidentiary assessment. 8. Supreme Court Ruling 153/2024, of 21 February 2024. Assessment of expert evidence. Scope and content. Are the findings of the opinions binding on the Courts? 9. Supreme Court Ruling 183/2024, of 29 February 2024. Computer damage. Art. 264(2) 1a) and c) and 2 in relation to art. 264.5 and 264(3) a) Penal Code. Concept of data and software. 10. Supreme Court Ruling 156/2024, of 22 February 2024. Difference between the concepts of minor significance and minor importance in crimes against public health. 11. Supreme Court Ruling 186/2024, of 29 February 2024. Crime of child abduction. Who can be the active subjects of this offence? 12. Supreme Court Ruling 241/2024, of 13 March 2024. Offence of assault and battery on a police officer. Evidentiary value of images obtained from images recorded by the media.